Characterization of Multidrug-Resistant Isolates of Salmonella enterica Serovars Heidelberg and Minnesota from Fresh Poultry Meat Imported to Portugal - Silveira, Leonor (2022)
Salmonella enterica serovars Heidelberg and Minnesota frequently display several genetic mobile elements making them potential spreaders of resistance genes. Here, we phenotypically determined the antibiotic resistance profile and subsequently performed whole-genome sequencing on 36 isolates recovered from samples of fresh poultry meat, within the Portuguese Official Inspection Plan for Imported Foodstuffs. Several isolates of both serovars showed high genetic relatedness either with isolates from raw poultry meat imported to the Netherlands from Brazil or with isolates from samples from the broiler production chain in Brazil. The multidrug-resistant (MDR) character was common to the vast majority (94.4%) of isolates from both serovars, and several isolates carried the plasmid IncA/C2 containing the β-lactamase gene blaCMY-2 and IncX1 containing a type IV secretion system. These results somehow mirror the scenario observed in the Netherlands, showing the introduction, through fresh imported poultry meat in compliance with European legislation, of MDR Salmonella enterica serovars Heidelberg and Minnesota in Europe, with the potential spread of resistance markers. These data suggest the need to revise the hygiene criteria for foodstuffs monitoring before its placement on the market, with the determination of the resistome being an invaluable contribute to limit the dissemination of resistance markers.